Protection provided by influenza vaccine against influenza-related hospitalisation in ≥65 year olds: Early experience of introduction of a newly licensed adjuvanted vaccine in England in 2018/19. Issue 2 (10th January 2020) - Pebody, Richard; Whitaker, Heather; Zhao, Hongxin; Andrews, Nick; Ellis, Joanna; Donati, Matthew; Zambon, Maria
Abstract: 2018/19 was the first season of introduction in England of a newly licensed adjuvanted influenza vaccine (aTIV) for adults 65 years or older, who were previously offered standard-dose, non-adjuvanted vaccine, achieving uptake levels >70%, often with poor effectiveness. This paper presents the end-of-season adjusted vaccine effectiveness (aVE) against laboratory confirmed influenza hospitalisation in this population. A frequency-matched test negative case control approach was used to estimate aVE by influenza A subtype and vaccine type. Cases were influenza confirmed hospitalisations and controls influenza negative hospitalisations who were 65 years or more. Cases and controls were selected from a sentinel laboratory surveillance system which collates details of inpatients and outpatients routinely tested on clinical advice for influenza infection with reverse-transcription polymerase chain reaction (RT-PCR) on respiratory samples. Vaccine and clinical history was obtained from the general practitioners of study participants. A total of 428 cases and 1013 controls were included in the analysis. End-of-season any-influenza aVE against hospitalisation was 53.4% (95% CI: 39.9, 63.9). By influenza A subtype, aVE was 64.8% (95% CI: 49.6, 75.3) against influenza A(H1N1)pdm09 and 39.3% (95% CI: 6.5, 60.6) against influenza A(H3N2). There was insufficient data to estimate influenza B VE. aVE estimates for all influenza, influenza A(H1N1)pdm09 and influenza A(H3N2) for aTIV were 53.8% (39.8, 64.5); 65.9% (50.6, 76.4) and 39.5% (4.8, 61.5) respectively. We provide evidence of significant influenza VE in the elderly, most notably against influenza A(H1N1)pdm09, but also against A(H3N2) for aTIV.